Inovação ambiental: das imprecisões conceituais a uma definição comum no âmbito da gestão ambiental pró-ativa - Angelo, Fernanda Dias; Jabbour, Charbel José Chiappetta [UNESP]; Galina, Simone Vasconcelos Ribeiro (My University, 2011)
The objective of this paper is to propose a common definition for the term “Environmental Innovation”, starting with a systematic literature review, encompassing some of the most significant articles in this Field. The definition of Environmental Innovation proposed in this paper involves the main dimensions, motivations and barriers to the effectiveness of Environmental Innovation as a practice in organizations. We consider Environmental Innovation an essential issue for proactive environmental management. As a result, the authors expect to present a systematic definition of Environmental Innovation, which is of increasing relevance to the transition towards a more sustainable society.

O objetivo deste artigo é propor uma definição comum ao termo “Inovação Ambiental”, partindo-se de uma sistematização de literatura, englobando alguns dos mais expressivos artigos da área. A definição de inovação ambiental proposta neste artigo, envolve as principais dimensões, motivações e barreiras à efetividade da Inovação Ambiental, enquanto prática nas organizações. Considera-se que a Inovação Ambiental é pressuposto da Gestão Ambiental proativa. Como resultado, espera-se apresentar uma definição sistematizada sobre o conceito de inovação ambiental, que é de crescente relevância para a transição rumo a uma sociedade mais sustentável.
Keywords: Environmental innovation; Environmental management; Concept; Barriers; Inovação ambiental; Gestão ambiental; Conceito; Barreiras